STRATEGI WANPRESTASI DALAM PEMBIAYAAN KEPEMILIKAN RUMAH PADA AKAD MUSYRAKAH MUTANAQISAH DI BANK KALBAR CABANG SYARIAH SAMBAS - Sri Devi; Sulastri (Cross-Border Journal of Business Management, 2026)
This research aims to analyze the default handling strategy and the factors causing defaults in home ownership financing using the Musyarakah Mutanaqisah contract at Bank Kalbar Sambas Sharia Branch. This research employs a qualitative approach with a descriptive research type and a case study design. Data collection was carried out through in-depth interviews with bank management and staff, customers experiencing defaults, direct observation at the research site, and official bank documentation. The results show that the implemented default handling strategy is carried out in stages, starting with a persuasive approach and customer guidance according to collectibility levels, followed by restructuring in the form of rescheduling, reconditioning, and voluntary collateral execution without increasing the customer’s principal obligation burden. Factors causing defaults include unstable economic conditions and income, limited location access and payment facilities, poor character and financial management skills of customers, and family problems. The implemented strategy is aligned with sharia principles, yet improvements are still needed in the initial verification stage for prospective customers and expansion of payment service coverage.